Inventarisasi Jenis Tanaman Rempah Dan Pemanfaatannya Di Dusun Air Terjun Desa Paya Tampah, Aceh Tamiang - Apriyanti, Dewi; Suwardi , Adi Bejo (Biosel Biology Science and Education, 2024)
This research aims to inventory the spice plants planted by the community and provide an understanding of the importance of using natural spices that are healthier and more sustainable for the community in Air Terjun Hamlet. This research uses an exploratory qualitative approach with direct observation and interview techniques. Based on findings in both yards and gardens, 12 types of spice plants were found consisting of 7 families, namely Zingiberaceae, Poaceae, Lamiaceae, Myrtaceae, Rutaceae, Pandanaceae and Piperaceae which are commonly used by the community. The part that is often used is the rhizome at 45% and the highest use value (UV) is 1.00 in the species ginger (Zingiber officinale), turmeric (Curcuma domestica), lemongrass (Cymbopogon citratus), bay leaves (Syzygium polyanthum), curry leaves (Murraya koenigii).  Keywords: Inventory, Spice plants, Use value (UV)